Segmented joint
Patent Information
- Application Number
- JP2025059958
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
- Estimated Expiration
- 2045-03-31
AI Technical Summary
【0010】 本発明の一実施形態によれば、曲がりの抑制されたセグメント接合体が提供される。曲がりの抑制されたセグメント接合体は耐熱衝撃性及び圧縮強度が有意に向上することから、大型化が進展しているDPF及びGPF等のフィルタに特に好適に利用可能である。
Smart Images

Figure 2026166782000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a segment joint having a plurality of honeycomb structure segments whose sides are joined to each other via a bonding material. [Background technology]
[0002] Particulate matter (hereinafter referred to as PM) in exhaust gases emitted from internal combustion engines such as diesel and gasoline engines contains soot. Soot is harmful to human health and its emission is regulated. Currently, in order to comply with exhaust gas regulations, porous ceramic filters with a columnar honeycomb structure, such as DPFs and GPFs, are widely used to filter out PM such as soot by passing exhaust gas through porous ceramic partitions.
[0003] In order to use such filters continuously over a long period of time, it is necessary to regenerate them. That is, in order to eliminate the increased pressure loss caused by PM (particulate matter) accumulating inside the filter over time, it is necessary to burn off the accumulated PM inside the filter. However, this filter regeneration process generates significant thermal stress, and this thermal stress can cause defects such as cracks and fractures in the filter.
[0004] In response to the demand for improved thermal shock resistance against such thermal stress, filters with a segment structure have been proposed that have the function of dispersing and mitigating thermal stress by joining the sides of multiple honeycomb structure segments with a bonding material to form a segment joint, and further attempts have been made to improve their thermal shock resistance.
[0005] However, in recent years, there has been a growing demand for larger filters, which has also increased the thermal stress generated during regeneration. To prevent the aforementioned defects, there is a strong need for improved thermal shock resistance. However, because filters are made of porous ceramics, they tend to bend more as they become longer due to their larger size. Methods to suppress filter bending have been known to date, such as adding a water-absorbing resin and a pore-forming material to the clay (Patent Document 1) and arranging a predetermined backplate on the inlet side of the die when extruding the molding material (Patent Document 2). [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Patent No. 4627498 [Patent Document 2] Japanese Patent Publication No. 2023-149427 [Overview of the project] [Problems that the invention aims to solve]
[0007] The methods described in Patent Documents 1 and 2 contribute to suppressing the amount of bending of the honeycomb molded body before firing. However, since bending during firing is not taken into consideration, there is room for improvement in terms of suppressing bending of the fired product. Furthermore, the methods described in Patent Documents 1 and 2 lack sufficient consideration for suppressing bending of the final product, the segmented joint. In other words, the fact that the segmented joint is composed of multiple honeycomb structure segments is not adequately considered. Developing a technology to suppress bending of the final product, the segmented joint, is expected to contribute to improving compressive strength in addition to thermal shock resistance, and would therefore be particularly beneficial in the filter field, where the size of filters is increasing.
[0008] In view of the above circumstances, the object of the present invention, in one embodiment, is to provide a segment joint in which bending is suppressed. [Means for solving the problem]
[0009] [Aspect 1] A segmented joint, The segment assembly has a plurality of honeycomb structure segments, each having at least one planar side surface joined to the others via a bonding material. Each of the aforementioned honeycomb structure segments has a first segment bottom surface, a second segment bottom surface, and at least one planar side surface connecting the first segment bottom surface and the second segment bottom surface, and also has a porous ceramic partition wall that divides a plurality of cells extending from the first segment bottom surface to the second segment bottom surface. Each of the aforementioned multiple honeycomb structure segments satisfies the following condition: Smax (in mm) is the maximum amount of curvature of each of the at least one planar side surfaces used to join adjacent honeycomb structure segments, and L (in mm) is the length of the line segment connecting the centroid of the bottom surface of the first segment and the centroid of the bottom surface of the second segment, such that Smax / L ≤ 0.010. Segment assembly. [Aspect 2] The segment joint according to embodiment 1, wherein each of the plurality of honeycomb structure segments has an Smax of 2.0 mm or less. [Aspect 3] The segment joint according to embodiment 1, wherein each of the plurality of honeycomb structure segments has an Smax of 1.0 mm or less. [Aspect 4] The segment joint according to embodiment 1 or 2, wherein each of the plurality of honeycomb structure segments has an L of 50 to 350 mm. [Aspect 5] The segment joint has a cylindrical outer shape with an outer peripheral surface, a first circular base, and a second circular base. With the line segment connecting the center of gravity of the first circular bottom surface and the center of gravity of the second circular bottom surface as the central axis, the same radial distance from the central axis to the outer peripheral side surface at the height position 10mm inward from the first circular bottom surface in the direction in which the central axis extends, the height position 10mm inward from the second circular bottom surface in the direction in which the central axis extends, and the height position of the midpoint of the central axis are defined as R1, R2, and R3 respectively, and Fmax is defined as |R3-(R1+R2) / 2| in the radial direction where the absolute value of |R3-(R1+R2) / 2| is maximum, the segment joined body according to any one of aspects 1 to 4, wherein Fmax is 2.0mm or less. [Aspect 6] The segment joined body according to aspect 5, wherein Fmax is 1.0mm or less. [Aspect 7] The segment joined body according to any one of aspects 1 to 6, wherein the isostatic fracture strength is 1.0MPa or more. [Aspect 8] After heating the segment joined body in an electric furnace at a set temperature for 60 minutes (when the volume of the segment joined body is 5L or less) or 120 minutes (when the volume of the segment joined body exceeds 5L), taking it out from the electric furnace and allowing it to cool to room temperature, the step of visually checking whether a crack with a length of 3mm or more has occurred in the segment joined body is repeated with the initial set temperature being 200°C and the set temperature being increased by 50°C each time until a crack can be confirmed, the segment joined body according to any one of aspects 1 to 7, wherein the set temperature at which a crack can be confirmed is 250°C or higher. [Aspect 9] The segment joined body according to any one of aspects 1 to 8, wherein each of the plurality of honeycomb structure segments has a thermal conductivity at 50°C of 3W / (m·K) or more as measured by the disk heat flow meter method in accordance with ASTM E1530. [Aspect 10] The segment joined body according to any one of aspects 1 to 9, wherein each of the plurality of honeycomb structure segments has an average linear expansion coefficient measured in accordance with JIS R1618:2002 when the temperature is changed from 40°C to 800°C of 5.5×10 -6 / K or less. [Aspect 11] The segment joint according to any one of embodiments 1 to 10, wherein each of the plurality of honeycomb structure segments has a porosity of 70% or less. [Aspect 12] The segment joint according to embodiment 11, wherein each of the plurality of honeycomb structure segments has a porosity of 30% or more and 70% or less. [Aspect 13] The segment assembly according to any one of embodiments 1 to 12, wherein each of the plurality of honeycomb structure segments contains 70 parts by mass or more of silicon carbide per 100 parts by mass of the total of silicon carbide and silicon. [Aspect 14] The segment assembly according to embodiments 1 to 13, wherein each of the plurality of honeycomb structure segments contains silicon oxide, strontium oxide, and aluminum oxide, and the aluminum oxide content is 1.0% or more relative to the total mass of silicon oxide, strontium oxide, and aluminum oxide. [Aspect 15] The segment assembly according to any one of embodiments 1 to 14, wherein each of the plurality of honeycomb structure segments contains 0.2 to 2.5 parts by mass of aluminum oxide per 100 parts by mass of silicon carbide and silicon in total. [Aspect 16] A segmented joint, The segment assembly has a plurality of rectangular parallelepiped honeycomb structure segments whose sides are joined to each other via a bonding material. Each of the plurality of rectangular parallelepiped honeycomb structure segments has a first segment side surface, a second segment side surface, a third segment side surface, a fourth segment side surface, a first segment bottom surface, and a second segment bottom surface, and has a porous ceramic partition wall that divides a plurality of cells extending from the first segment bottom surface to the second segment bottom surface. In each of the plurality of rectangular honeycomb structure segments, if the maximum amount of curvature among the curvature of the first segment side, the second segment side, the third segment side, and the fourth segment side used to join adjacent honeycomb structure segments is denoted as Smax (unit: mm), and the length of the line segment connecting the centroid of the bottom surface of the first segment and the centroid of the bottom surface of the second segment is denoted as L (unit: mm), then Smax / L ≤ 0.010 is satisfied. Segment assembly. [Aspect 17] The segment joint according to embodiment 16, wherein among the plurality of rectangular parallelepiped honeycomb structure segments, whose sides are joined to each other via a bonding material, there are at least two rectangular parallelepiped honeycomb structure segments whose sides having the greatest amount of curvature are aligned. [Aspect 18] The segment joint according to embodiment 17, wherein 30% or more of the total number of rectangular parallelepiped honeycomb structure segments, whose sides are joined to each other via a bonding material, have the orientation of the side having the greatest curvature coincide. [Aspect 19] The segment joint according to embodiment 17, wherein the orientation of the side surface having the maximum curvature is the same for all of the plurality of rectangular parallelepiped honeycomb structure segments, whose sides are joined to each other via a bonding material. [Effects of the Invention]
[0010] According to one embodiment of the present invention, a segment joint with suppressed bending is provided. Since the segment joint with suppressed bending has significantly improved thermal shock resistance and compressive strength, it is particularly suitable for use in filters such as DPFs and GPFs, which are becoming larger. [Brief explanation of the drawing]
[0011] [Figure 1A] This is a schematic bottom view of a segment joint according to one embodiment of the present invention. [Figure 1B]This is a schematic side view of a segment assembly according to one embodiment of the present invention. [Figure 2] A schematic perspective view of a honeycomb structure segment constituting a segment assembly according to one embodiment of the present invention is shown. [Figure 3] A schematic cross-sectional view is shown of a honeycomb structure segment constituting a segment joint according to one embodiment of the present invention, as observed from a cross-section parallel to the direction in which the cells extend. [Figure 4] A schematic diagram is shown to illustrate the measurement methods for R1, R2, and R3 of a segment joint having a cylindrical outer shape. [Figure 5] A schematic diagram is shown to illustrate a method for measuring the amount of curvature of honeycomb structure segments. [Modes for carrying out the invention]
[0012] Next, embodiments of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the following embodiments, and it should be understood that appropriate design changes, improvements, etc., can be made based on the ordinary knowledge of those skilled in the art, without departing from the spirit of the invention.
[0013] (1. Structure of the segment joint) A segment joint according to one embodiment of the present invention can be used, for example, as a filter such as a DPF (Diesel Particulate Filter) and a GPF (Gasoline Particulate Filter) that collects soot and is installed in the exhaust gas line from a combustion device, typically an engine mounted in a vehicle. The filter can be installed, for example, inside an exhaust pipe. A buffer mat can be interposed between the inner surface of the exhaust pipe and the filter to hold the filter inside the exhaust pipe.
[0014] Figure 1A shows a schematic bottom view of a segment joint 10 according to one embodiment of the present invention. Figure 1B shows a schematic side view of a segment joint 10 according to one embodiment of the present invention. The segment joint 10 has a first bottom surface 104 which serves as an inlet for exhaust gas and a second bottom surface 106 which serves as an outlet for exhaust gas. Exhaust gas flowing in from the first bottom surface 104 is purified as it passes through the segment joint 10 and discharged from the second bottom surface 106. The segment joint 10 has a structure in which the planar sides 102 of a plurality of honeycomb structure segments 100 are joined to each other via a joining material 107. By joining a plurality of honeycomb structure segments 100 to provide a segment joint 10, thermal shock resistance can be increased. The segment joint 10 may also have an outer peripheral wall 103 formed by grinding the outer peripheral part to a desired shape (e.g., cylindrical), applying a coating material to the outer peripheral side surface, and then drying and heat treating it.
[0015] In one embodiment, among the multiple honeycomb structure segments 100 constituting the segment joint 10, there are multiple rectangular parallelepiped honeycomb structure segments whose sides 102 are joined to each other via a bonding material 107. The number of rectangular parallelepiped honeycomb structure segments in the segment joint 10 is not limited, but can be, for example, 4 to 100, typically 9 to 81, and more typically 16 to 64. Also, the proportion of rectangular parallelepiped honeycomb structure segments among the honeycomb structure segments in the segment joint 10 is not limited, but can be, for example, 0 to 60%, typically 10 to 55%, and more typically 25 to 50%.
[0016] (2. Characteristics of segmented joints) The following describes some of the characteristics that a segment joint according to one embodiment of the present invention can exhibit. [2-1. Isostatic fracture strength] One measure of the compressive strength of a segment joint is its isostatic fracture strength. In measuring the isostatic fracture strength of a segment joint, the joint is submerged in water within a pressure vessel, and the water pressure is gradually increased to apply isotropic pressure to the joint. As the water pressure in the pressure vessel gradually increases, fracture eventually occurs in the bulkheads and outer walls of the segment joint. The pressure value (fracture strength) at which fracture occurs is the isostatic fracture strength. Isostatic fracture strength is measured according to the automotive standard (JASO M505-87) issued by the Japan Society of Automotive Engineers of Japan.
[0017] For applications as automotive exhaust gas filters and / or catalyst supports, a higher isostatic fracture strength of the segment joint is desirable. A segment joint according to one embodiment of the present invention can exhibit an isostatic fracture strength of 1.0 MPa or higher. More preferably, the segment joint can exhibit an isostatic fracture strength of 2.0 MPa or higher, and even more preferably, 5.0 MPa or higher. There is no particular upper limit set for the isostatic fracture strength of the segment joint, but considering the balance with manufacturing costs, it is usually 20 MPa or less, typically 15 MPa or less, and more typically 10 MPa or less. Therefore, a segment joint according to one embodiment of the present invention can exhibit an isostatic fracture strength of, for example, 1.0 to 20 MPa, preferably 2.0 to 15 MPa, and more preferably 5.0 to 10 MPa.
[0018] [2-2. Curve Amount] In one embodiment, the segment joint 10 has a cylindrical shape with an outer peripheral surface, a first circular base, and a second circular base. In this case, the outer peripheral surface of the segment joint 10 corresponds to the outer surface of the outer peripheral wall 103. The first circular base corresponds to the first base 104, and the second circular base corresponds to the second base 106. Let C be the central axis, defined as the line segment connecting the centroid O1 of the first base surface 104 and the centroid O2 of the second base surface 106. Let R1, R2, and R3 be the same radial distances from the central axis C to the outer surface of the outer wall 103 at heights 10 mm inward from the first base surface 104 in the direction extending along the central axis C, 10 mm inward from the second base surface 106 in the direction extending along the central axis C, and at the height of the midpoint of the central axis C. If Fmax is defined as the value of |R3-(R1+R2) / 2| in the radial direction where the absolute value of |R3-(R1+R2) / 2| is maximized, then an Fmax of 2.0 mm or less can be obtained (see Figure 4). A smaller Fmax indicates that the segment joint 10 has suppressed bending.
[0019] A segment joint according to one embodiment of the present invention can preferably exhibit an Fmax of 1.0 mm or less, and more preferably an Fmax of 0.8 mm or less. There is no particular lower limit set for Fmax, but it is usually 0.05 mm or more, typically 0.1 mm or more, and more typically 0.15 mm or more. Therefore, a segment joint according to one embodiment of the present invention can exhibit an Fmax of, for example, 0.05 to 2.0 mm, preferably 0.1 to 1.0 mm, and more preferably 0.15 to 0.8 mm.
[0020] Fmax is given as the maximum value obtained when the absolute value of |R3-(R1+R2) / 2| is measured at 3000 equally spaced points around the entire circumference of the segment joint using a laser displacement meter. In the example, a Micro-Epsilon model ILD2200-200 laser displacement meter was used.
[0021] Figure 4 shows a schematic diagram illustrating the method for measuring Fmax using a laser displacement meter 122. First, the segment assembly 10 to be measured is placed on a turntable 121, which is installed on a horizontal surface, with the first base surface 104 or the second base surface 106 facing downwards. When placing the segment assembly 10 on the turntable 121, the distance between the center of gravity O1 of the first base surface 104 or the center of gravity O2 of the second base surface 106 and the rotation axis of the turntable 121 does not necessarily have to be 0. Even if they are far apart, R1, R2, and R3 can be calculated geometrically, and some displacement meters can even calculate them automatically.
[0022] The turntable 121 is configured to rotate at a predetermined rotational speed around a vertically extending rotation axis by a drive means such as a servo motor. The servo motor can be equipped with an encoder for detecting displacement amounts such as the rotation angle of the turntable 121. The laser displacement meter 122 is attached to the support column 126 and is configured to move vertically by a drive means such as a motor.
[0023] Next, the height and orientation of the laser displacement meter 122 are adjusted to conditions suitable for measuring R1, R2, or R3. Then, while irradiating the surface of the outer wall 103 with the laser 124, 3000 points of R1, R2, or R3 are measured at equal intervals while the turntable 121 is rotated once. This measurement makes it possible to measure the change in R1, R2, or R3 of the segment joint 10 over one full rotation. The change in R1, R2, or R3 over one full rotation can be stored in the computer's memory or elsewhere in association with the rotation angle θ of the turntable 121. This makes it possible to associate R1, R2, or R3 with a specific radial direction on the surface of the outer wall 103. Similar measurements are performed by changing the height of the laser displacement meter 122 to measure R1, R2, and R3, and Fmax is calculated based on the absolute value of |R3-(R1+R2) / 2| in the same radial direction. The laser irradiation direction may be the normal direction to the surface of the outer wall 103, but R1, R2, or R3 can be calculated geometrically even in other directions, and some displacement sensors can calculate them automatically.
[0024] [2-3. ESP crack temperature] When an electric furnace spalling (E-sp) test is performed on a segment joint according to one embodiment of the present invention under the following conditions, the set temperature at which cracks can be confirmed is 250°C or higher, preferably 450°C or higher, and typically 250°C to 400°C. The electric furnace spalling test is a test in which the segment joint is heated in an electric furnace at a set temperature for 60 minutes (if the volume of the segment joint is 5L or less) or 120 minutes (if the volume of the segment joint is greater than 5L), then removed from the electric furnace, allowed to cool to room temperature, and then visually checked to see if a crack of 3 mm or longer has occurred in the segment joint. This is repeated starting from an initial temperature of 200°C, increasing the set temperature by 50°C increments until a crack can be confirmed, and the set temperature at which a crack can be confirmed is measured. The volume of the segment joint is calculated based on the external dimensions of the segment joint (e.g., bottom area × total length).
[0025] (3. Composition of honeycomb structure segments) Figure 2 shows a schematic perspective view of a honeycomb structure segment 100 constituting a segment joint according to one embodiment of the present invention. Figure 3 shows a schematic cross-sectional view of the honeycomb structure segment 100 constituting a segment joint according to one embodiment of the present invention, observed in a cross section parallel to the direction in which the cells extend.
[0026] In one embodiment, the honeycomb structure segment 100 has a first segment bottom surface 104S, a second segment bottom surface 106S, and at least one planar side surface 102 connecting the first segment bottom surface 104S and the second segment bottom surface 106S. When the honeycomb structure segment 100 is observed from the side of the first segment bottom surface 104S or the second segment bottom surface 106S, it is typical that at least one planar side surface 102 extends in a straight line, and two adjacent planar side surfaces 102 extend in a straight line perpendicular to each other from a common vertex. The honeycomb structure segment 100 shown in Figure 2 is a rectangular parallelepiped as a whole, and the outer surface of the outer peripheral side wall 113 is composed of the first segment side surface 102A, the second segment side surface 102B, the third segment side surface 102C, and the fourth segment side surface 102D.
[0027] In one embodiment, the honeycomb structure segment 100 has an outer peripheral side wall 113 and a porous ceramic partition wall 112 disposed inside the outer peripheral side wall 113, which divides a plurality of cells 108, 110 that extend parallel from the bottom surface 104S of the first segment to the bottom surface 106S of the second segment.
[0028] Each cell 108, 110 may penetrate from the first segment bottom surface 104S to the second segment bottom surface 106S by having both the first segment bottom surface 104S and the second segment bottom surface 106S open. However, in order to improve PM collection performance, it is preferable that the honeycomb structure segment 100 has a plurality of first cells 108 that extend from the first segment bottom surface 104S to the second segment bottom surface 106S, with the first segment bottom surface 104S open and the second segment bottom surface 106S sealed, and a plurality of second cells 110 that are adjacent to at least one first cell 108, extend from the first segment bottom surface 104S to the second segment bottom surface 106S, with the first segment bottom surface 104S sealed and the second segment bottom surface 106S open. In this case, the honeycomb structure segment 100 can be arranged so that the first cells 108 and the second cells 110 are alternately adjacent to each other with a partition wall 112 in between, so that both bottom surfaces exhibit a checkerboard pattern.
[0029] When exhaust gas containing soot is supplied to the bottom surface 104S of the first segment on the upstream side of the honeycomb structure segment 100, the exhaust gas is introduced into the first cell 108 and proceeds downstream within the first cell 108. Since the bottom surface 106S of the second segment on the downstream side of the first cell 108 is sealed, the exhaust gas permeates through the porous ceramic partition wall 112 that separates the first cell 108 and the second cell 110 and flows into the second cell 110. Since the soot cannot permeate the partition wall 112, it is collected and deposited within the first cell 108. After the soot is removed, the clean exhaust gas that has flowed into the second cell 110 proceeds downstream within the second cell 110 and flows out from the bottom surface 106S of the second segment on the downstream side.
[0030] The outer shape of the honeycomb structure segment 100 is generally columnar. For example, it may be a column with a polygonal base, or a column with a base composed of a combination of curves and line segments. Examples of polygons include quadrilaterals (rectangles, squares, etc.) and hexagons. In a typical embodiment, the outer shape of the honeycomb structure segment 100 can be a rectangular parallelepiped.
[0031] When a honeycomb structure segment 100 according to one embodiment is observed from the side of the first segment bottom surface 104S or the second segment bottom surface 106S, the side surface 102 of the honeycomb structure segment 100 is composed of a curve that constitutes an arc, a first line segment extending from one end of the curve, and a second line segment extending from the other end of the curve, which extends in a direction perpendicular to the first line segment (100A in Figure 1A). When a honeycomb structure segment 100 according to another embodiment is observed from the side of the first segment bottom surface 104S or the second segment bottom surface 106S, the side surface 102 of the honeycomb structure segment 100 is composed of a curve that constitutes an arc, a first line segment extending from one end of the curve, a second line segment extending from the other end of the curve, and a third line segment connecting the first and second line segments, which extends in a direction perpendicular to both the first and second line segments (100B in Figure 1A).
[0032] The size of the honeycomb structure segment 100 is, for example, the base area of 600 to 3600 mm². 2 It can be, typically 900-2500mm 2 It can be done this way.
[0033] The length L (in mm) of the line segment connecting the centroid G1 of the first segment base 104S and the centroid G2 of the second segment base 106S can be, for example, 50 to 350 mm, and is typically 100 to 250 mm. Within the above length range, from the viewpoint of the effect of improving thermal shock resistance by suppressing bending that is easily apparent, the length in the direction in which the cells of the honeycomb structure segment 100 extend is preferably 178 mm or more and 250 mm or less, more preferably 203 mm or more and 200 mm or less, and even more preferably 254 mm or more and 150 mm or less.
[0034] There are no restrictions on the shape of the cells in a cross-section perpendicular to the direction of extension (height direction) of the first cell 108 and the second cell 110, but they are preferably square, hexagonal, octagonal, or a combination thereof. Among these, square and hexagonal are preferred. By shaping the cells in this way, when the honeycomb structure segment 100 is used as a particulate filter, the pressure loss when exhaust gas is passed through it is reduced, resulting in superior purification performance.
[0035] Means for suppressing the bending of the segment joint 10 include (1) means for suppressing the bending of each of the multiple honeycomb structure segments 100 that constitute the segment joint 10, and (2) means for suppressing the overall bending of the segment joint 10 by devising the arrangement of the multiple honeycomb structure segments 100 that constitute the segment joint 10. Either (1) or (2) may be adopted, but it is preferable to combine both means.
[0036] First, let me explain the method in (1). In one embodiment, each of the multiple honeycomb structure segments 100 constituting the segment joint 10 has at least one planar side surface 102 used for joining adjacent honeycomb structure segments. Each honeycomb structure segment 100 has a curved portion on the planar side surface 102 used for joining adjacent honeycomb structure segments. In another embodiment, each of the multiple rectangular honeycomb structure segments 100 constituting the segment joint 10 has at least one of its first segment side surface 102A, second segment side surface 102B, third segment side surface 102C, and fourth segment side surface 102D used to join adjacent honeycomb structure segments. The first segment side surface 102A, second segment side surface 102B, third segment side surface 102C, and fourth segment side surface 102D are all planar side surfaces 102. The first segment side surface, second segment side surface, third segment side surface, and fourth segment side surface used to join adjacent honeycomb structure segments each have a degree of curvature. In any embodiment, it is preferable that Smax (in mm) is the maximum amount of curvature of at least one side surface used to join adjacent honeycomb structure segments in each honeycomb structure segment 100, and that L (in mm) is the length of the line segment connecting the centroid G1 of the first segment bottom surface 104S and the centroid G2 of the second segment bottom surface 106S, such that Smax / L ≤ 0.010. It is more preferable that Smax / L ≤ 0.008 is satisfied for each of the multiple rectangular honeycomb structure segments 100, and even more preferable that Smax / L ≤ 0.005 is satisfied. It is desirable that Smax / L be as small as possible, but considering the balance with manufacturing costs, it is usually 0.001 ≤ Smax / L, typically 0.002 ≤ Smax / L, and more typically 0.003 ≤ Smax / L. Therefore, for each of the multiple rectangular honeycomb structure segments 100, it is preferable, for example, that 0.001 ≤ Smax / L ≤ 0.010 be satisfied, more preferably that 0.002 ≤ Smax / L ≤ 0.008 be satisfied, and even more preferably that 0.003 ≤ Smax / L ≤ 0.005 be satisfied.
[0037] The amount of curvature of the planar side surface used to join adjacent honeycomb structure segments is measured by the following procedure. For example, if the honeycomb structure segment 100 is rectangular, the segment joint 10 is CT scanned using an X-ray CT scanner to obtain cross-sectional images of the honeycomb structure segment 100 to be measured, parallel to the direction in which the cells extend, with the first segment side surface 102A and the third segment side surface 102C (a pair of opposing sides) located at both the left and right ends, and the cross-sectional image at the center of the honeycomb structure segment 100 in the depth direction, and the second segment side surface 102B and the fourth segment side surface 102D (the other pair of opposing sides) located at both the left and right ends, and the cross-sectional image at the center of the honeycomb structure segment 100 in the depth direction (see Figure 5). Based on the cross-sectional images, the distance D (= amount of curvature) between the straight line Q connecting the upper and lower ends of the first segment side surface 102A and the tangent line P that is parallel to the straight line Q and furthest from the straight line Q is determined. Similarly, the distance D (= amount of curvature) is determined for the second segment side 102B, the third segment side 102C, and the fourth segment side 102D, and the maximum value of distance D is calculated as the maximum amount of curvature (Smax). If the honeycomb structure segment 100 is not rectangular, the amount of curvature can be similarly measured by performing a CT scan so that the planar side 102, which is the target of the curvature measurement, extends in the depth direction (from front to back) in the cross-sectional image.
[0038] It is also desirable that Smax itself be small. Therefore, each of the multiple honeycomb structure segments 100 constituting the segment joint 10 preferably has an Smax of 2.0 mm or less, more preferably 1.0 mm or less, and even more preferably 0.5 mm or less. It is desirable that Smax be as small as possible, but due to the trade-off with manufacturing costs, it is usually 0.1 mm or more, typically 0.3 mm or more, and more typically 0.4 mm or more. Therefore, each of the multiple honeycomb structure segments 100 constituting the segment joint 10 preferably has an Smax of, for example, 0.1 to 2.0 mm, more preferably 0.3 to 1.0 mm, and even more preferably 0.4 mm to 0.5 mm.
[0039] Next, the means of (2) will be described. As mentioned above, the segment joint 10 according to one embodiment of the present invention includes a plurality of rectangular parallelepiped honeycomb structure segments 100 in which the sides 102 are joined to each other via a joining material 107. Since it is difficult to make all of the first segment side 102A, second segment side 102B, third segment side 102C, and fourth segment side 102D that constitute each rectangular parallelepiped honeycomb structure segment 100 flat, it is possible to identify the side having the largest amount of curvature Smax from among them. In this case, when a plurality of honeycomb structure segments are joined to each other with the orientation of the side having the largest amount of curvature Smax aligned, the joint width becomes uniform and stress concentration can be avoided, resulting in improved thermal shock resistance and isostatic fracture strength.
[0040] Accordingly, the segment joint 10 according to one embodiment of the present invention has at least two rectangular parallelepiped honeycomb structure segments 100 in which the orientation of the side surface 102 having the maximum amount of curvature coincides, among a plurality of rectangular parallelepiped honeycomb structure segments 100 in which the side surfaces 102 of which have the maximum amount of curvature coincides. In a preferred embodiment, 30% or more, more preferably 50% or more, and even more preferably 80% or more of the total number of rectangular parallelepiped honeycomb structure segments 100 in the segment joint 10 have the orientation of the side surface 102 having the maximum amount of curvature coincides. In the most preferred embodiment, the orientation of the side surface 102 having the maximum amount of curvature coincides for all of the plurality of rectangular parallelepiped honeycomb structure segments 100 in the segment joint 10.
[0041] The material for the honeycomb structure segment 100 is not limited to porous ceramics. Examples of ceramics include cordierite, mullite, zirconium phosphate, aluminum titanate, silicon carbide, silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zirconia, spinel, indialite, sapphirin, corundum, titania, and silicon nitride. These ceramics may be contained individually or in combination of two or more. Other materials for the honeycomb structure segment 100 include porous sintered metals containing alloy components mainly composed of one or more elements selected from the group consisting of Fe, Cr, Mo, and Ni.
[0042] Among the porous ceramics mentioned above, silicon-silicon carbide composites are suitable for filter applications because they possess excellent properties such as heat resistance, thermal shock resistance, and oxidation resistance. Silicon-silicon carbide composites contain silicon carbide particles as aggregate and silicon as a binder to hold the silicon carbide particles together. Preferably, multiple silicon carbide particles are bound together by silicon in such a way that pores are formed between them.
[0043] However, silicon-silicon carbide composites are prone to bending due to shrinkage during firing. Furthermore, if the porosity is high, the amount of bending increases, making segment bending more likely during firing. When multiple honeycomb structure segments 100 are joined together with a bonding agent, if the amount of bending of each honeycomb structure segment 100 is large, it becomes difficult to select which segments can be joined. Moreover, when the segment joint is formed through the joining and coating processes, the bending tends to increase even further. Therefore, when the honeycomb structure segment 100 contains silicon-silicon carbide composites, typically when it contains 50% by mass or more of silicon-silicon carbide composites, more typically when it contains 60% by mass or more of silicon-silicon carbide composites, and even more typically when it contains 70% by mass or more of silicon-silicon carbide composites, it is necessary to optimize the blending ratio of silicon and silicon carbide, as well as the type and blending ratio of firing aids, so that bending is suppressed.
[0044] Specifically, for the reason that bending is easily suppressed, the honeycomb structure segment 100 preferably contains 70 parts by mass or more of silicon carbide per 100 parts by mass of total silicon carbide and silicon, more preferably 75 parts by mass or more, and even more preferably 80 parts by mass or more. On the other hand, from the viewpoint of improving thermal conductivity and strength, the honeycomb structure segment 100 preferably contains 95 parts by mass or less of silicon carbide per 100 parts by mass of total silicon carbide and silicon, more preferably 90 parts by mass or less, and even more preferably 85 parts by mass or less. Therefore, for example, the honeycomb structure segment 100 preferably contains 70 parts by mass or more and 95 parts by mass or less of silicon carbide per 100 parts by mass of total silicon carbide and silicon, more preferably 75 parts by mass or more and 90 parts by mass or less, and even more preferably 80 parts by mass or more and 85 parts by mass or less.
[0045] Furthermore, the honeycomb structure segment 100 preferably contains silicon oxide, strontium oxide, and aluminum oxide as firing aids to improve thermal conductivity and strength by making the metallic silicon easier to melt. In this case, since the amount of silicon melted can be controlled, the honeycomb structure segment 100 preferably contains 1.0% or more of aluminum oxide relative to the total mass (100%) of silicon oxide, strontium oxide, and aluminum oxide, more preferably 3.0% or more, and even more preferably 6.0% or more. However, if the aluminum oxide content becomes too high, the thermal conductivity and strength tend to decrease. For this reason, the honeycomb structure segment 100 preferably contains 15.0% or less of aluminum oxide relative to the total mass (100%) of silicon oxide, strontium oxide, and aluminum oxide, more preferably 12.0% or less, and even more preferably 9.0% or less. Therefore, the honeycomb structure segment 100 preferably contains aluminum oxide in an amount of, for example, 1.0 to 15.0%, more preferably 3.0 to 12.0%, and even more preferably 6.0 to 9.0%, relative to the total mass (100%) of silicon oxide, strontium oxide, and aluminum oxide.
[0046] From the viewpoint of suppressing bending, it is preferable to control the content of silicon oxide, strontium oxide, and aluminum oxide in terms of their proportion to the total mass of silicon carbide and silicon. Specifically, each of the multiple rectangular parallelepiped honeycomb structure segments constituting the honeycomb joint, preferably all of the multiple honeycomb structure segments constituting the honeycomb joint, preferably contains 5.0 to 35.0 parts by mass of silicon oxide, more preferably 8.0 to 25.0 parts by mass, and even more preferably 11.0 to 20.0 parts by mass, of silicon oxide per 100 parts by mass of the total silicon carbide and silicon. Furthermore, each of the honeycomb structure segments preferably contains 0.0 to 10.0 parts by mass of strontium oxide, more preferably 1.0 to 7.0 parts by mass, and even more preferably 2.0 to 5.0 parts by mass, of strontium oxide per 100 parts by mass of the total silicon carbide and silicon. Furthermore, each honeycomb structure segment preferably contains 0.2 to 2.5 parts by mass of aluminum oxide per 100 parts by mass of total silicon carbide and silicon, more preferably 0.5 to 2.0 parts by mass, and even more preferably 1.0 to 1.5 parts by mass.
[0047] Not making the porosity of the honeycomb structure segment 100 too high is also advantageous in suppressing bending. Specifically, the upper limit of the porosity of each of the multiple rectangular honeycomb structure segments constituting the honeycomb joint, preferably all of the multiple honeycomb structure segments constituting the honeycomb joint, is preferably 70% or less, more preferably 60% or less, and even more preferably 50% or less. Not making the porosity of the honeycomb structure segment 100 too high is also advantageous in ensuring strength and thermal conductivity. However, in order to prevent the pressure loss when gas is flowed through from rising too high, the lower limit of the porosity of the honeycomb structure segment 100 is preferably 30% or more, more preferably 40% or more, and even more preferably 45% or more. Therefore, the porosity of the honeycomb structure segment 100 is preferably, for example, 30-70%, more preferably 40-60%, and even more preferably 45-50%.
[0048] Here, the porosity of the honeycomb structure segment 100 is given as the average value obtained when multiple samples of the partition walls 112 constituting the honeycomb structure segment 100 are taken without bias from the honeycomb structure segment 100 and the porosity of each sample is measured by the mercury intrusion method. Specifically, the porosity is calculated by the mercury intrusion method (in accordance with JIS R 1655:2003).
[0049] The average thickness of the partition walls 112 in the honeycomb structure segment 100 is preferably 0.1 mm to 0.5 mm, although this is not limiting. The strength of the honeycomb structure segment 100 can be ensured by making the average thickness of the partition walls 112 preferably 0.1 mm or more, and more preferably 0.2 mm or more. Furthermore, by making the average thickness of the partition walls 112 preferably 0.5 mm or less, and more preferably 0.4 mm or less, the pressure loss when exhaust gas is passed through the honeycomb structure segment 100 can be kept low.
[0050] In this specification, the thickness of a partition wall refers to the length of the line segment that crosses the partition wall when the centroids of adjacent cells are connected by a line segment perpendicular to the direction in which the cell extends. The average thickness of a partition wall refers to the average value of the thicknesses of all partition walls in each honeycomb structure segment.
[0051] The cell density of honeycomb structure segments is 50-400 cells / square inch (7.7-62.0 cells / cm²). 2 Preferably, the density is 70-370 cells / square inch (10.8-57.3 cells / cm²). 2 It is more preferable that the density is 80-320 cells / square inch (12.4-49.6 cells / cm²). 2 It is even more preferable that the cell density of the honeycomb structure segment be 50 cells / square inch (7.7 cells / cm²). 2 If the cell density of the honeycomb structure segment is less than 400 cells / square inch (62.0 cells / cm²), sufficient strength may not be obtained. 2If it exceeds ), the pressure loss becomes too high, which may lead to a decrease in engine output when used as a DPF. In this specification, cell density is the value obtained by dividing the number of cells by the area of one bottom surface of the honeycomb structure segment (the bottom surface of the first segment or the bottom surface of the second segment) (the total area of the partitions and cells excluding the outer peripheral side walls).
[0052] In each honeycomb structure segment, the average thickness of the outer peripheral sidewall 113 is not limited, but considering the balance between the strength and filter performance of the honeycomb structure segment 100, it can be, for example, 0.1 mm to 0.5 mm, and preferably 0.15 mm to 0.4 mm. In this specification, the average thickness of the outer peripheral sidewall refers to the average value obtained when the thickness of multiple locations on the outer peripheral sidewall is measured without bias in a cross section perpendicular to the direction in which the cell extends.
[0053] (4. Characteristics of honeycomb structure segments) The following describes some of the characteristics that a honeycomb structure segment according to one embodiment of the present invention can exhibit.
[0054] [4-1. Thermal conductivity] The higher the thermal conductivity of the honeycomb structure segment, the more the occurrence of temperature differences inside the honeycomb structure segment is suppressed, so that the thermal shock resistance is improved. In addition, a higher thermal conductivity of the honeycomb structure segment can improve the removal performance when PM trapped in the honeycomb structure segment is burned and removed for filter regeneration. In this regard, the honeycomb structure segment according to one embodiment of the present invention can exhibit high thermal conductivity. Specifically, each of the plurality of rectangular parallelepiped honeycomb structure segments constituting the honeycomb joined body, desirably all of the plurality of honeycomb structure segments constituting the honeycomb joined body, has a thermal conductivity at 50°C measured by the disk heat flow meter method in accordance with ASTM E1530 of 3 W / (m·K) or more, preferably 10 W / (m·K) or more, and more preferably 20 W / (m·K) or more. No particular upper limit is set for the thermal conductivity, but in consideration of the balance with manufacturing cost, it is usually 40 W / (m·K) or less, typically 30 W / (m·K) or less, and more typically 25 W / (m·K) or less. Accordingly, each of the honeycomb structure segments can exhibit the thermal conductivity of, for example, 3 to 40 W / (m·K), preferably 10 to 30 W / (m·K), and more preferably 20 to 25 W / (m·K).
[0055] The measurement of the thermal conductivity of the honeycomb structure segment is performed by the following procedure. A prismatic sample with a size of 35 mm × 35 mm × 20 mm (length in the cell extending direction) is cut out from the central portion in the radial direction and the height direction of the honeycomb structure segment, and the thermal conductivity of the sample is measured under the above-mentioned temperature conditions using a measuring instrument conforming to ASTM E1530, which is taken as the measured value.
[0056] [4-2. Average Linear Expansion Coefficient (CTE)] It is desirable that the thermal expansion of the honeycomb structure segment is small. Specifically, each of the plurality of rectangular parallelepiped honeycomb structure segments constituting the honeycomb joined body, desirably all of the plurality of honeycomb structure segments constituting the honeycomb joined body, has an average linear expansion coefficient measured in accordance with JIS R1618:2002 when the temperature is changed from 40°C to 800°C of 5.5×10 -6It is preferable that the average coefficient of thermal expansion is 5.5 × 10⁻⁶. -6 By keeping the temperature below 10°C, thermal stress during exhaust gas treatment and filter regeneration, when the temperature of the honeycomb structure segment increases, is reduced, significantly improving thermal shock resistance. The average coefficient of linear expansion is 5.4 × 10°C. -6 It is more preferable that it be less than or equal to / K, 5.3 × 10 -6 It is even more preferable that the average linear expansion coefficient is less than or equal to / K. There is no particular lower limit to the average linear expansion coefficient, but from the viewpoint of ease of manufacture, the average linear expansion coefficient is 3.0 × 10⁻⁶. -6 It is preferable that it be 3.5 × 10 -6 It is more preferable that the value be 4.0 × 10 -6 It is even more preferable that the average coefficient of linear expansion is 3.0 × 10⁻⁶. -6 / K or more 5.5×10 -6 It is preferable that it be less than or equal to / K, and 3.5 × 10 -6 / K or more 5.4×10 -6 It is more preferable that it be less than or equal to / K, and 4.0 × 10 -6 / K or more 5.3×10 -6 It is even more preferable that it be less than or equal to / K.
[0057] The average linear expansion coefficient of a honeycomb structure segment is measured using the following procedure: A prismatic sample measuring 3 mm × 3 mm × 15 mm (length in the direction of cell extension) is cut from the center of the honeycomb structure segment in both the radial and vertical directions. The average linear expansion coefficient of this sample is measured under the temperature change conditions described above and recorded as the measured value.
[0058] (5. Bonding material) The bonding material 107 serves to join the side surfaces 102 of the honeycomb structure segments 100 together. In one embodiment, the bonding material 107 is interposed in layers between the side surfaces 102 of the honeycomb structure segments 100 that are facing each other. The thickness of the bonding material 107 (the length of the bonding material in the direction perpendicular to the joining surface with the honeycomb structure segments) is determined considering the bonding force (shear strength) between the honeycomb structure segments 100, and is appropriately selected, for example, in the range of 0.5 to 3.0 mm.
[0059] In one embodiment, the bonding material 107 is porous. When the bonding material 107 is porous, a higher porosity makes it easier to obtain thermal shock resistance due to the stress relaxation effect. For this reason, the lower limit of the porosity of the bonding material is preferably 40% or more, more preferably 50% or more, and even more preferably 60% or more. However, from the viewpoint of ensuring bonding strength, the upper limit of the porosity of the bonding material is preferably 80% or less, more preferably 75% or less, and even more preferably 70% or less. Accordingly, the porosity of the bonding material is preferably, for example, 40 to 80%, more preferably 50 to 75%, and even more preferably 60 to 70%.
[0060] The porosity of the bonding material was determined by taking multiple samples of the bonding material without bias from the segmented joint 10 and measuring the total pore volume (unit: cm³) using the mercury intrusion method (in accordance with JIS R 1655:2003). 3 ( / g) and apparent density by Archimedes method in water (unit: g / cm³) 3 It is calculated from the above. In other words, the porosity here is the porosity before the catalyst is supported.
[0061] The bonding material may contain one or more ceramics or other inorganic substances such as cordierite, mullite, alumina, silica, alumina silicate, volastonite, mica, zirconium phosphate, aluminum titanate, silicon carbide, silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zirconia, spinel, indialite, sapphirin, corundum, titania, and silicon nitride. If the honeycomb structure segment 100 contains a silicon-silicon carbide composite, the bonding material preferably contains silicon carbide, alumina silicate, mullite, or alumina.
[0062] (6. Method for manufacturing segmented joints) In the first embodiment, the method for manufacturing a segment joint according to the present invention is as follows: Step 1 involves preparing a plurality of columnar honeycomb structure segments made of porous ceramics, each having an outer peripheral side wall and partition walls on the inner peripheral side of the outer peripheral side wall that divide a plurality of cells extending from a first bottom surface to a second bottom surface. Step 2 involves joining the sides of the multiple columnar honeycomb structure segments made of porous ceramics using a joining slurry, and drying the joining slurry. Includes.
[0063] In step 1, multiple honeycomb structure segments made of porous ceramics are prepared, each having an outer peripheral side wall and partition walls on the inner periphery of the outer peripheral side wall that divide multiple cells extending from the first bottom surface to the second bottom surface. These porous ceramic honeycomb structure segments can be manufactured by modifying a part of the manufacturing process, following known methods for manufacturing honeycomb structures, and the procedure is illustrated below.
[0064] First, a raw material composition containing ceramic raw materials, a dispersion medium, a pore-forming material, and a binder is kneaded to prepare a clay body. Then, the clay body is extruded and dried to produce a honeycomb molded body. Additives such as dispersants can be added to the raw material composition as needed. When extruding, a die having the desired overall shape, cell shape, partition wall thickness, cell density, etc., can be used.
[0065] In the drying process, conventional drying methods such as hot air drying, microwave drying, dielectric drying, reduced pressure drying, vacuum drying, and freeze-drying can be used. Among these, a drying method combining hot air drying with microwave drying or dielectric drying is preferred because it can dry the entire molded body quickly and uniformly. The pore seal portion can be formed by forming the pore seal portion at predetermined positions on both bottom surfaces of the dried honeycomb molded body and then drying the pore seal portion.
[0066] Ceramic raw materials are the materials that remain after firing metal oxides and metals, etc., and constitute the framework of the columnar honeycomb molded body (columnar honeycomb structure) after firing as ceramics. Therefore, firing aids are also a type of ceramic raw material. Ceramic raw materials can be provided, for example, in powder form. Examples of ceramic raw materials include cordierite, mullite, zirconium phosphate, aluminum titanate, silicon carbide, silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zirconia, spinel, indialite, sapphirin, corundum, titania, and silicon nitride. Specifically, although not limited to these, examples include silicon carbide, silicon, silica, talc, alumina, kaolin, serpentine, pyroferrite, brucite, boehmite, mullite, magnesite, and aluminum hydroxide. In addition, silicon oxide, strontium oxide, and aluminum oxide added as firing aids are also a type of ceramic raw material. The ceramic raw materials may be used individually or in combination of two or more types.
[0067] Examples of dispersion media include water, or a mixed solvent of water and an organic solvent such as alcohol, but water is particularly suitable.
[0068] The porosity-forming material is not particularly limited as long as it becomes pore after firing, and examples include wheat flour, starch, foamed resin, superabsorbent resin, silica gel, carbon (e.g., graphite, coke), ceramic balloons, polyethylene, polystyrene, polypropylene, nylon, polyester, acrylic, phenol, etc. The porosity-forming material may be used alone or in combination of two or more types. From the viewpoint of increasing the porosity of the honeycomb structure, the content of the porosity-forming material is preferably 1 part by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, per 100 parts by mass of ceramic raw material. From the viewpoint of ensuring the strength of the honeycomb structure, the content of the porosity-forming material is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of ceramic raw material.
[0069] Examples of binders include organic binders such as methylcellulose, hydroxypropyl methylcellulose, hydroxyethylcellulose, carboxymethylcellulose, and polyvinyl alcohol. In particular, the combined use of methylcellulose and hydroxypropyl methylcellulose is preferred. Furthermore, from the viewpoint of increasing the strength of the honeycomb molded body before firing, the binder content is preferably 4 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 6 parts by mass or more, per 100 parts by mass of ceramic raw material. From the viewpoint of suppressing the occurrence of cracking due to abnormal heat generation during the firing process, the binder content is preferably 9 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 7 parts by mass or less, per 100 parts by mass of ceramic raw material. The binder may be used alone or in combination of two or more types.
[0070] Dispersants such as ethylene glycol, dextrin, fatty acid soap, and polyether polyol can be used. The dispersant may be used individually or in combination of two or more types. The dispersant content is preferably 0 to 2 parts by mass per 100 parts by mass of ceramic raw material.
[0071] When sealing the bottom surface of a honeycomb molded body, the method is not particularly limited, and a well-known method such as filling the cell openings of the bottom surface, to which a predetermined mask has been applied, with a sealing slurry can be employed. There are no particular restrictions on the material of the sealing portion, but it is preferable to use ceramics from the viewpoint of strength and heat resistance. Preferably, the ceramics are those containing one or more of the following: cordierite, mullite, zirconium phosphate, aluminum titanate, silicon carbide, silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zirconia, spinel, indialite, sapphirin, corundum, titania, silicon nitride, etc. Preferably, the sealing portion is formed of a material containing a total of 50% by mass or more of these ceramics, and more preferably of a material containing 80% by mass or more. It is even more preferable that the sealing portion has the same material composition as the main body of the honeycomb molded body, as this allows for the same expansion rate during firing and leads to improved durability.
[0072] Honeycomb structure segments can be manufactured by performing a degreasing process and a firing process on the dried honeycomb molded body. The conditions for the degreasing and firing processes can be those known according to the material composition of the honeycomb molded body and do not require special explanation, but specific examples of conditions are given below.
[0073] The degreasing process will now be explained. The combustion temperature of the binder is approximately 200°C, and the combustion temperature of the porosity-forming material is approximately 300-1000°C. Therefore, the degreasing process can be carried out by heating the honeycomb molded body to a temperature range of approximately 200-1000°C. The heating time is not particularly limited, but it is usually around 10-100 hours. The honeycomb molded body after the degreasing process is called a calcined body.
[0074] The firing process depends on the material composition of the honeycomb molded body, but for example, it can be carried out by heating the calcined body to 1350-1600°C in an atmospheric environment and holding it for 3-10 hours.
[0075] In order to suppress bending of the columnar honeycomb structure segments produced in this manner, it is important to minimize the amount of shrinkage of the honeycomb molded body during firing. Specifically, the shrinkage rate (before firing / after firing) of the honeycomb molded body during firing is preferably 1.000 to 1.040 in the overall length direction and 1.000 to 1.050 in the radial direction, more preferably 1.000 to 1.020 and 1.000 to 1.030 in the radial direction, and even more preferably 1.000 to 1.010 and 1.000 to 1.020 in the radial direction. The shrinkage rate in the overall length direction is calculated by measuring the change in the length L of the line segment connecting the centroid G1 of the bottom surface 104S of the first segment and the centroid G2 of the bottom surface 106S of the second segment before and after firing using a caliper. The radial shrinkage rate is calculated by measuring the change in length of the line segment M connecting the centroids G3 and G4 of each of the two opposing pairs of side surfaces 102 before and after firing using a caliper, and the larger value is taken as the measured value.
[0076] In order to reduce the shrinkage rate during firing, it is preferable to take measures to adjust firing conditions such as making the particle size of the ceramic raw material powder fine and uniform (e.g., median diameter of 1 to 50 μm by laser diffraction / scattering method), firing temperature (e.g., 1400 to 2000°C), holding time (e.g., 1 to 5 hours), and atmosphere composition (e.g., inert atmosphere). In particular, when the aim is to produce columnar honeycomb structure segments containing silicon-silicon carbide composite material, as mentioned above, it is important to optimize the mixing ratio of silicon and silicon carbide, as well as the type and mixing ratio of firing aids.
[0077] Other methods to suppress bending of honeycomb structure segments include lowering the firing temperature and reducing the amount of binder used.
[0078] In step 2, the sides of multiple columnar honeycomb structure segments made of porous ceramics are joined together using a joining slurry, and the joining slurry is dried. This transforms the joining slurry into a bonding material, and a segment joint is produced. Specifically, the segment joint can be manufactured by the following procedure: With a film to prevent bonding material adhesion attached to both bottom surfaces of each honeycomb structure segment, the bonding material is applied to the joining surface (side). Next, these segments are placed adjacent to each other so that their sides face each other, and the adjacent segments are pressed together and then heated and dried. In this way, a segment joint is produced in which the sides of adjacent segments are joined together by the bonding material.
[0079] The material of the film for preventing adhesion of bonding material is not particularly limited, but synthetic resins such as polypropylene (PP), polyethylene terephthalate (PET), polyimide, or Teflon (registered trademark) can be suitably used. Furthermore, the film preferably has an adhesive layer, and the material of the adhesive layer is preferably an acrylic resin, a rubber resin (for example, rubber mainly composed of natural rubber or synthetic rubber), or a silicone resin.
[0080] As a bonding slurry, for example, one can be prepared by mixing anisotropic inorganic powder, aggregate, pore-forming material, dispersion medium (e.g., water), and, if necessary, additives such as binders and dispersants.
[0081] As the material for the anisotropic inorganic powder, natural minerals or artificial ceramic fibers may be used. Suitable natural minerals include needle-shaped or plate-shaped natural minerals such as volastonite, mica, talc, sepiolite, palygoskite, and attapulgite. Suitable artificial ceramic fibers include RCF (amorphous refractory ceramic fiber mainly composed of alumina and silica), alumina fibers, mullite fibers, carbon fibers, silicon carbide fibers, boron nitride fibers, potassium titanate fibers, and zinc oxide fibers. The anisotropic inorganic powder may be used alone or in combination of two or more types.
[0082] Examples of aggregate materials include ceramics such as cordierite, mullite, zirconium phosphate, aluminum titanate, silicon carbide, silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zirconia, spinel, indialite, sapphirin, corundum, titania, and silicon nitride.
[0083] Either an inorganic binder or an organic binder may be used. Examples of organic binders include methylcellulose, hydroxypropoxylmethylcellulose, carboxymethylcellulose, polyvinyl alcohol, and methylcellulose. Examples of inorganic binders include clay minerals such as bentonite, montmorillonite, sepiolite, and attapulgite. One type of binder may be used, or two or more types may be used in combination.
[0084] A dispersant such as polyethylene glycol oleate may be added to the bonding slurry.
[0085] Examples of pore-forming materials include hollow or solid organic balloons such as foamed resins, water-absorbent resins, organic materials such as starch, and inorganic materials such as fly ash balloons. One type of pore-forming material may be used, or two or more types may be used in combination.
[0086] If the solid content concentration of the bonding slurry is too low, the bonding width will be thin, while if it is too high, the bonding width will be thick. For this reason, the solid content concentration of the bonding slurry is preferably 50 to 90% by mass, more preferably 60 to 80% by mass, and even more preferably 65 to 75% by mass.
[0087] For the segment joint produced by the above procedure, the outer periphery may be ground to form a desired shape (e.g., cylindrical), a coating material may be applied to the outer surface, and then the outer wall may be formed by drying and heat treatment. For drying and heat treatment, conditions such as heating in an air atmosphere at 400 to 700°C, preferably 500 to 600°C, for 0.5 to 3 hours, preferably 0.5 to 1 hour can be used. The coating material is not particularly limited, and known outer periphery coating materials can be used. Examples of outer periphery coating materials include those obtained by mixing inorganic raw materials such as inorganic fibers, colloidal silica, clay, and ceramic particles with additives such as organic binders, foaming resins, and dispersants, and water to form a slurry. Furthermore, the method of applying the outer periphery coating material is not particularly limited, and known methods can be used.
[0088] The filter may be supported with a catalyst appropriate to its application. An example of a method for supporting a catalyst on a filter is to introduce a catalyst slurry into the cell by a conventionally known suction method or the like, allow it to adhere to the surface and pores of the partition wall, and then subject it to a high-temperature treatment to bake the catalyst contained in the catalyst slurry onto the partition wall.
[0089] Catalysts, though not limited to specific applications, include oxidation catalysts (DOC) that oxidize and burn hydrocarbons (HC) and carbon monoxide (CO) to increase exhaust gas temperature, PM combustion catalysts that assist in the combustion of PM such as soot, and nitrogen oxides (NOx). x SCR catalysts and NSR catalysts for removing ) and hydrocarbons (HC), carbon monoxide (CO) and nitrogen oxides (NO xA ternary catalyst capable of simultaneously removing ( ) is mentioned. The catalyst may appropriately contain, for example, noble metals (Pt, Pd, Rh, etc.), alkali metals (Li, Na, K, Cs, etc.), alkaline earth metals (Ca, Ba, Sr, etc.), rare earth metals (Ce, Sm, Gd, Nd, Y, La, Pr, etc.), transition metals (Mn, Fe, Co, Ni, Cu, Zn, Zr, Sc, Ti, V, Cr, etc.).
[0090] In particular, in DPFs for passenger cars, soot collection and NO x To simultaneously provide a purification function, SCR catalysts such as Cu-substituted zeolite and Fe-substituted zeolite are supported on the DPF. In this case, NO is produced by ammonia obtained by decomposing urea on board the vehicle. x It can perform purification. [Examples]
[0091] The following examples illustrate the present invention and its advantages, but the present invention is not limited to these examples.
[0092] <Examples 1-6, Comparative Examples 1-3> (1. Fabrication of honeycomb structure segments) Silicon carbide (SiC) powder, silicon (Si) powder, silicon oxide (SiO2) powder, strontium oxide (SrO) powder, and aluminum oxide (Al2O3) powder were mixed in the mass proportions listed in Table 1 according to the test number. A pore-forming agent (starch), an organic binder (hydroxypropyl methylcellulose), and a surfactant (oleic acid ester) were added to this mixture in the mass proportions listed in Table 1, and then an appropriate amount of water was added to obtain a clay mixture. The median diameters of the silicon carbide (SiC) powder, silicon (Si) powder, and pore-forming agent, measured by laser diffraction and scattering methods, are listed in Table 1.
[0093] [Table 1]
[0094] This clay was extruded through a predetermined die and dried to obtain a rectangular parallelepiped honeycomb molded body having an outer peripheral side wall and partitions that divide a plurality of cells extending from the first bottom surface to the second bottom surface. On this rectangular parallelepiped honeycomb molded body, a sealing portion was formed at one end of each cell so that both bottom surfaces exhibited a checkerboard pattern. That is, the sealing portions were formed so that adjacent cells were sealed at opposite ends. The same material as the columnar honeycomb molded body was used for the sealing portions. After forming the sealing portions and drying, the columnar honeycomb molded body was degreased in an air atmosphere at approximately 450°C, and then fired in an Ar atmosphere at approximately 1450°C to bond the SiC particles in the molded body with Si, thereby obtaining a rectangular parallelepiped honeycomb structure segment with the following specifications.
[0095] Base shape: 35mm square The total length (L, the length of the line segment connecting the centroid of the base of the first segment and the centroid of the base of the second segment) is shown in Table 3. Porosity: As shown in Table 2 Average thickness of the partition wall: 0.305 mm Cell cross-sectional shape: square Cell density: 44 cells / cm² 2 Average thickness of the outer perimeter sidewall: 0.5 mm Composition: As shown in Table 2 (Composition analysis was performed using X-ray fluorescence and inert gas fusion method.)
[0096] Furthermore, Table 3 shows the results of measuring the shrinkage rate (overall length and radial direction) of the honeycomb molded body during firing for each test number using the method described above. The number of honeycomb structure segments for each test number was produced in the number necessary to manufacture the segment joint described later, and Table 3 shows the average values.
[0097] (2. Preparation of bonding slurry) Next, anisotropic inorganic powder (mullite fiber), aggregate (silicon carbide, cordierite), pore-forming material (foamed resin), binder (carboxymethylcellulose), and dispersant (PEG monophosphate ester) were mixed in a mixer to obtain a bonding slurry (solid content concentration = 73% by mass).
[0098] (3. Manufacturing of segmented joints) This bonding slurry was applied to the sides of the rectangular honeycomb structure segments obtained in the above manufacturing procedure to a thickness of approximately 1 mm. Another honeycomb structure segment obtained in the above manufacturing procedure was then placed on top, and this process was repeated to create a segment laminate consisting of a total of 16 honeycomb structure segments arranged in a 4x4 grid. The entire laminate was then bonded together by applying external pressure as needed, and then dried at 120°C for 2 hours to obtain a segment laminate. In the segment laminate, the sides of multiple rectangular honeycomb structure segments are joined together via the bonding material.
[0099] When assembling the segmented joint, the proportion of the 16 rectangular honeycomb structure segments, each joined to the others via a bonding material, in which the orientation of the side with the greatest curvature coincided was varied according to the test number, as shown in Table 3.
[0100] The outer circumference of the segment joint was ground to make its shape cylindrical. A coating material with the same composition as the joining slurry was then applied to the machined surface to reshape the outer wall. The joint was then dried and cured in an air atmosphere at 600°C for 2 hours to obtain the final segment joint (160 mmφ) for each test example. The number of rectangular honeycomb segments in the segment joint was 4. The thickness of the joining material was approximately 1.1 mm. Only the number of segment joints necessary for conducting the evaluation tests described below were manufactured.
[0101] (4. Characteristics of segmented joints) The segment joints obtained above were evaluated for the following characteristics mentioned earlier. The results are shown in Table 3. (1) Maximum curvature of the honeycomb structure segment Smax For each honeycomb structure segment constituting the segment joint for each test number, the maximum bending amount Smax was measured according to the method described above. The maximum value among the multiple Smax values measured for each honeycomb structure segment is shown as “Smax” in Table 3. The ratio of “Smax” to the total length L (Smax / L) is also shown in Table 3. (2) Bending Fmax of the segment joint (3) Thermal conductivity at 50°C (Measured by selecting any segment before joining, but the same value is obtained when measured on the joined body.) (4) Average coefficient of linear expansion (CTE) when the temperature is varied from 40°C to 800°C (Measurements were taken on an arbitrary segment before joining, but the same value is obtained when measured on the joined body.) (5) Isostatic fracture strength (iso strength) (6) ESP crack temperature Furthermore, the porosity of the bonding material was approximately 70% for all segmented joints.
[0102] [Table 2]
[0103] [Table 3] [Explanation of Symbols]
[0104] 10: Segment joint 100: Honeycomb structure segment 102: Side view 102A: Side view of the first segment 102B: Side view of the second segment 102C: Third segment side view 102D: Side view of the fourth segment 103:Outer wall 104: First bottom surface 104S: Bottom of the first segment 106:Second bottom surface 106S: Bottom of the second segment 107: Bonding material 108: Cell 1 110: Cell 2 112: Bulkhead 113: Outer perimeter side wall 121: Turntable 122: Laser displacement meter 124: Laser 126: Post
Claims
1. A segmented joint, The segment assembly has a plurality of honeycomb structure segments, each having at least one planar side surface joined to the others via a bonding material. Each of the aforementioned honeycomb structure segments has a first segment bottom surface, a second segment bottom surface, and at least one planar side surface connecting the first segment bottom surface and the second segment bottom surface, and also has a porous ceramic partition wall that divides a plurality of cells extending from the first segment bottom surface to the second segment bottom surface. Each of the aforementioned multiple honeycomb structure segments satisfies the following condition: Smax (in mm) is the maximum amount of curvature of each of the at least one planar side surfaces used to join adjacent honeycomb structure segments, and L (in mm) is the length of the line segment connecting the centroid of the bottom surface of the first segment and the centroid of the bottom surface of the second segment, such that Smax / L ≤ 0.
010. Segment assembly.
2. The segment joint according to claim 1, wherein each of the plurality of honeycomb structure segments has a Smax of 2.0 mm or less.
3. The segment joint according to claim 1, wherein each of the plurality of honeycomb structure segments has a Smax of 1.0 mm or less.
4. The segment joint according to claim 1 or 2, wherein each of the plurality of honeycomb structure segments has an L of 50 to 350 mm.
5. The segment joint has a cylindrical outer shape with an outer peripheral surface, a first circular base, and a second circular base. With the line segment connecting the centroid of the first circular bottom surface and the centroid of the second circular bottom surface as the central axis, the same radial distance from the central axis to the outer peripheral side surface at the height position 10 mm inward from the first circular bottom surface in the direction in which the central axis extends, the height position 10 mm inward from the second circular bottom surface in the direction in which the central axis extends, and the height position of the midpoint of the central axis is respectively defined as R 2 , 3 , 1 , R 2 and R 3 , and when the absolute value of |R 3 -(R 1 +R 2 ) / 2| is maximized in the radial direction, and the value of |R 3 -(R 1 +R 2 ) / 2| in this radial direction is defined as Fmax, the segment joined body according to claim 1 or 2, wherein Fmax is 2.0 mm or less.
6. The segment joint according to claim 5, wherein Fmax is 1.0 mm or less.
7. The segment joint according to claim 1 or 2, wherein the isostatic fracture strength is 1.0 MPa or more.
8. The segment joint according to claim 1 or 2, wherein the segment joint is heated in an electric furnace at a set temperature for 60 minutes (if the volume of the segment joint is 5 L or less) or 120 minutes (if the volume of the segment joint is greater than 5 L), then removed from the electric furnace, allowed to cool to room temperature, and then visually inspected to see if a crack of 3 mm or longer has occurred in the segment joint, and this step is repeated with an initial temperature of 200°C, increasing the set temperature by 50°C increments until a crack can be confirmed, the set temperature at which a crack can be confirmed is 250°C or higher.
9. The segment joint according to claim 1 or 2, wherein each of the plurality of honeycomb structure segments has a thermal conductivity of 3 W / (m·K) or more at 50°C, as measured by a disk heat flow meter according to ASTM E1530.
10. Each of the aforementioned honeycomb structure segments has an average coefficient of thermal expansion of 5.5 × 10⁻¹⁰ when the temperature is varied from 40°C to 800°C, as measured according to JIS R1618:2002. -6 A segment joint according to claim 1 or 2, wherein the value is less than or equal to / K.
11. The segment joint according to claim 1 or 2, wherein each of the plurality of honeycomb structure segments has a porosity of 70% or less.
12. The segment joint according to claim 11, wherein each of the plurality of honeycomb structure segments has a porosity of 30% or more and 70% or less.
13. The segment assembly according to claim 1 or 2, wherein each of the plurality of honeycomb structure segments contains 70 parts by mass or more of silicon carbide with respect to 100 parts by mass of silicon carbide and silicon in total.
14. The segment assembly according to claim 1 or 2, wherein each of the plurality of honeycomb structure segments contains silicon oxide, strontium oxide, and aluminum oxide, and the aluminum oxide is present in an amount of 1.0% or more relative to the total mass of silicon oxide, strontium oxide, and aluminum oxide.
15. The segment assembly according to claim 1 or 2, wherein each of the plurality of honeycomb structure segments contains 0.2 to 2.5 parts by mass of aluminum oxide per 100 parts by mass of silicon carbide and silicon in total.
16. A segmented joint, The segment assembly has a plurality of rectangular parallelepiped honeycomb structure segments whose sides are joined to each other via a bonding material. Each of the plurality of rectangular parallelepiped honeycomb structure segments has a first segment side surface, a second segment side surface, a third segment side surface, a fourth segment side surface, a first segment bottom surface, and a second segment bottom surface, and has a porous ceramic partition wall that divides a plurality of cells extending from the first segment bottom surface to the second segment bottom surface. In each of the plurality of rectangular honeycomb structure segments, if the maximum amount of curvature among the curvature of the first segment side, the second segment side, the third segment side, and the fourth segment side used to join adjacent honeycomb structure segments is denoted as Smax (unit: mm), and the length of the line segment connecting the centroid of the bottom surface of the first segment and the centroid of the bottom surface of the second segment is denoted as L (unit: mm), then Smax / L ≤ 0.010 is satisfied. Segment assembly.
17. The segment joint according to claim 16, wherein among the plurality of rectangular honeycomb structure segments, whose sides are joined to each other via a bonding material, there are at least two rectangular honeycomb structure segments whose sides having the greatest amount of curvature are aligned.
18. The segment joint according to claim 17, wherein 30% or more of the total number of rectangular parallelepiped honeycomb structure segments, whose sides are joined to each other via a bonding material, have the orientation of the side having the maximum curvature coincide.
19. The segment joint according to claim 17, wherein for all of the plurality of rectangular parallelepiped honeycomb structure segments, whose sides are joined to each other via a bonding material, the orientation of the side having the maximum amount of curvature is the same.
Citation Information
Patent Citations
Honeycomb structure, manufacturing method for the same, and shape adjustment method for honeycomb molding
JP2023149427A
Method for manufacturing a honeycomb structure
JP4627498B2